2010
DOI: 10.1007/s12034-010-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structure refinement of layered double hydroxides of Co, Mg and Ni with Ga

Abstract: Homogeneous precipitation by urea hydrolysis results in the formation of highly ordered layered double hydroxides of divalent metal ions (Co, Mg, Ni) and Ga. Structure refinement shows that these carbonate containing layered hydroxides crystallize with rhombohedral symmetry (space group R-3m) in the structure of the 3R 1 polytype. An analysis of the structure shows that, coulombic attraction between the layer and interlayer remains invariant in different layered hydroxides, whereas the strength of hydrogen bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…The calculated peaks are well consistent with the experimental one, confirming the rationality of the simulation (Figure b). In addition, the lattice parameters are similar to those reported CoGa LDH in the literature except for the Co/Ga ratio . The formula of the CoGa LDH in this work was thus determined to be [Co 3.8 Ga(OH) 9.6 ](CO 3 ) 0.5 · x H 2 O.…”
Section: Resultssupporting
confidence: 77%
“…The calculated peaks are well consistent with the experimental one, confirming the rationality of the simulation (Figure b). In addition, the lattice parameters are similar to those reported CoGa LDH in the literature except for the Co/Ga ratio . The formula of the CoGa LDH in this work was thus determined to be [Co 3.8 Ga(OH) 9.6 ](CO 3 ) 0.5 · x H 2 O.…”
Section: Resultssupporting
confidence: 77%
“…The projection on the isotropic dimension (F1) shows a single peak in the region for octahedral Ga, i.e. a single site, as is expected for MgGa LDH's [26]. The line shape in the anisotropic (F2) dimension is distorted in the 3QMAS spectrum due to the fairly large quadrupole interaction.…”
Section: Pxrd and Irmentioning
confidence: 54%
“…Mn-LDH and finally because the ionic radius of Ga 3+ (0.76 Å)75 is close to that of Mn 3+ (0.78Å). As shown by the authors of this previous study,74 the strength of the coulombic attraction and hydrogen bonding between the layer and…”
mentioning
confidence: 53%
“…The refined M−OH 2.0410( 7 74 The comparison with the Co 4 Ga 2 (OH) 12 CO 3 •3H 2 O sample is particularly interesting, first, because of the presence of cobalt, second because the M 2+ /M 3+ ratio is equal to 2 like in Co 3 Mn-LDH, and finally because the ionic radius of Ga 3+ (0.76 Å) 75 is close to that of Mn 3+ (0.78 Å). As shown by the authors of this previous study, 74 All these characterizations converge to highlight a unique result never reported so far. Many papers on Co R Mn-LDH have investigated a wide range of Co/Mn ratios, but most of them have neither been reported nor discussed their chemical compositions in terms of oxidation states.…”
Section: ■ Results and Discussionmentioning
confidence: 99%